2019
DOI: 10.1002/aur.2170
|View full text |Cite
|
Sign up to set email alerts
|

Time perception and autistic spectrum condition: A systematic review

Abstract: Problems with timing and time perception have been suggested as key characteristics of autism spectrum condition (ASC). Studies and personal accounts from clinicians, parents, caregivers, and self‐reports from autistic people themselves often refer to problems with time. Although a number of empirical studies have examined aspects relating to time in autistic individuals, there remains no clear consensus on whether or how timing mechanisms may be affected in autism. A key reason for this lack of clarity is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 108 publications
1
56
2
Order By: Relevance
“…This discrepancy may relate to the developmental changes that occur during and after adolescence (cf. Casassus et al 2019). Indeed, Stevenson et al (2018a) found that the temporal acuity for audio-visual information improved until around middle age and then declined with age in older individuals.…”
Section: Discussionmentioning
confidence: 98%
“…This discrepancy may relate to the developmental changes that occur during and after adolescence (cf. Casassus et al 2019). Indeed, Stevenson et al (2018a) found that the temporal acuity for audio-visual information improved until around middle age and then declined with age in older individuals.…”
Section: Discussionmentioning
confidence: 98%
“…On the one hand, the autistic self is highly centered on itself, showing an abnormally high degree of ego-centeredness as manifest in social isolation and loneliness, inability to read the emotions, feelings, and facial expressions of others [ 30 , 31 , 32 ], and major deficits in social cognition like theory of mind [ 5 , 6 , 7 ]. Such high ego-centeredness is, on the other hand, contrasted by weak self-referentiality with decreased use of “I” in language [ 33 , 34 , 35 ], no mention of own internal states, e.g., own emotion [ 10 , 36 , 37 ], own theory of mind [ 27 , 38 , 39 ], changes in time processing like duration estimation of shorter and longer time intervals as deficits in connecting different time points [ 40 , 41 , 42 ], decreased introspection [ 43 , 44 ], decrease in interoception [ 45 , 46 , 47 ], and reduced autobiographical memory [ 1 , 2 , 3 , 4 ] (see though Markram and Markram, 2012 [ 48 ], as well as Lind et al, 2020 [ 49 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of timing and temporal processing in movement disorders is well established (2). Alterations in aspects of temporal processing and timing have also been identified in many other neuropsychiatric conditions (1,(20)(21)(22)(23)(24). The therapeutic value of temporally based interventions (e.g., rhythmic cueing, slow rhythmic drumming) has been demonstrated for multiple neuropsychiatric conditions (25)(26)(27)(28).…”
Section: Figurementioning
confidence: 99%